Different Flaps For Oral And Maxillofacial Reconstruction: Review Of Literature And A Clinical Guide To The Clinicians (Journal of Pharmaceutical Negative Results, 2023)
There are different methods documented for reconstructing the oral and maxillofacial (OMF) region among which is the use of flaps (local or distant). New techniques of OMF reconstruction aim to restore function as well as improve aesthetics. This article intends to review the literature on different flaps used in oral and maxillofacial surgery (OMFS) and summarize their precise clinical use, taking into consideration the ease, difficulties, and the ultimate clinical outcomes. A review of the literature of local or distant flaps used in OMFS was done using Google database. There are many different methods of reconstruction in patients who have had defect in the OMF region. It is important for the OMF surgeon who is involved in the management of such patients to have an expertise concerning the selection of flap used to reconstruct such defects.